CALCIUM CONSUMPTION IN ADOLESCENT FOOTBALL PLAYERS LINKED TO THE NEW ASUNTION STAR CLUB DURING THE APRIL MONTH OF 2018. (Fiep Bulletin - online, 2020)
The growing participation of young people in football is a motivation for coaches, physical trainers and parents to know what are the special requirements to practice this sport safely, especially nutritional requirements. During childhood and adolescence, a balance is sought between nutritional status, exercise and physical growth. The food must meet the energy and nutrient requirements to enhance physical growth and maturation, physical activity, academic performance and maintain a reserve to meet the needs of the pubertal growth or strain. Calcium is an essential mineral for bone strengthening, especially in the pubertal stage, so it is imperative to ensure its proper consumption with the diet. Hypocalcaemia is uncommon in healthy children and adolescents, and the primary need for dietary calcium is to ensure bone growth and health. Objectives To assess the average calcium consumption of dairy sources in adolescent soccer players linked to the New Star Club of the city of Asunción in April 2018. Materials and methods The study had a non-experimental design, with a quantitative approach, descriptive scope and cross section in which 37 teenage soccer players who attended the New Star Club participated. The instrument to collect the data was a research file designed for this purpose, which included personal data of the subjects of study, and the Food Consumption Frequency Questionnaire, which is one of the most used methods in food history, taking As an advantage the simple and cheap. Results The average calcium value of dairy sources consumed by adolescents in the sample was 614 ± 209 mg / day, less than half of the required value of 1300 mg / day. Daily calcium consumption from dairy sources reflects a wide difference between 78% of inadequate or insufficient consumption compared to only 22% of adequate consumption. Discussion Coinciding with Barranco, Gisela Ivon, who found that 106 child soccer players in the 1999 category between 10 and 11 years old had an average calcium intake of 813.03 ± 347.48, with 1495 mg being the highest value consumed. Conclusion 78% of adolescents have inadequate or insufficient calcium intake. These data reveal the importance of promoting a nutritional education in schools, colleges and sports venues thus avoiding the risks involved in sports with poor nutrition.